Fetal malnutrition and its impacts on neonatal outcome in preterm infants - Korkmaz, Ayşe; Tekşam, Özlem; Yurdakök, Murat; Yiğit, Şule; Tekinalp, Gülsevin (The Turkish Journal of Pediatrics, 2011)
Fetal malnutrition is an important risk factor for both early and late neonatal outcome and adult diseases. In this study, we aimed to investigate the incidence and characteristics of fetal malnutrition and its impacts on early neonatal morbidity and mortality in preterm infants by using the clinical assessment of nutritional status score (CANSCORE). Preterm infants whose gestational ages were between 28-34 weeks were included in the study. Detailed prenatal and natal history, anthropometric measurements, and intrauterine growth status were defined, and CANSCORE was applied to all infants. Infants were separated into two groups according to total score as malnourished (total score < 25) and well nourished (total score > or = 25). Early and late neonatal morbidities, which were observed during the clinical progress, were noted in all infants. A total of 93 preterm infants were enrolled in the study. The incidence of fetal malnutrition was 54.8% (n = 51) in all infants. The incidences of maternal hypertension and preeclampsia, oligohydramnios and disturbed umbilical artery Doppler flow in the prenatal period and the incidences of neonatal hypoglycemia, polycythemia, feeding intolerance, and necrotizing enterocolitis in the postnatal period were significantly higher in preterm infants with fetal malnutrition. Fetal malnutrition contributes significantly to many early and late neonatal morbidities in preterm infants, and it should be identified in every preterm infant in the first days of life for predicting neonatal outcome, even though they are appropriately grown.